Intervening Perilaku Tidak Etis pada Implementasi Good Governance dan Locus of Control Terhadap Kecenderungan Kecurangan (Fraud) Akuntansi - Putu Mita Budiyanti; Nyoman Trisna Herawati (Universitas Pendidikan Ganesha, 2022)
This Study Aims To Determine The Effect Between Good Governance Implementation And Locus Of Control Toward The Accounting Fraud Tendency With Unethhical Behavior As Intervening Variable On LPD In Buleleng District. The Research Method Used Was Quantitative Research.The Population Was 146 LPD Employees In Buleleng District. Sample Of 45 People Was Taken Through A Purposive Sampling Technique. Data Analysis Was Assisted By The SPSS Program Version 20.0.The Research Indicate: (1) The Implementation Of Good Governance Negatively And Significantly Influences Unethical Behavior And The Tendency Of Accounting Fraud, (2) Locus Of Control Positively And Significantly Influences Unethical Behavior And The Tendency Of Accounting Fraud, (3) The Implementation Of Good Governance Negatively And Significantly Influences The Tendency Of Accounting Fraud With Unethical Behavior As Intervening Variable, (4) Locus Of Control Positively And Significantly Influences The Tendency Of Accounting Fraud With Unethical Behavior As Intervening Variable.